Analysis Of Factors Affecting The Performance Of Village Government Officials In The Implementation Of Government Tasks Village In Lebong Atas Sub-District Lebong District - Sanupil, Peri; Soleh , Ahmad; Abi , Yudi Irawan (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2024)
The aim of this research is to determine the factors that influence the performance of village government officials in carrying out village government duties in Upper Lebong District, Lebong Regency. The sample in this study was 56 village officials in Lebong Atas District, Lebong Regency. Data were collected using a questionnaire and the analysis methods used were multiple linear regression, determination tests and hypothesis tests The results of the regression analysis show Y = 1.132 + 0.295X1 + 0.333 X2 + 0.341X3. This illustrates a positive regression direction, meaning that there is a positive influence between X1 (motivation), X2 (education) and X3 (work discipline) on performance (Y). This means that if the variables of motivation, education and work discipline increase, the newspaper's performance will improve. The coefficient of determination is 0.780. This means that X1 (motivation), X2 (education) and education) and X3 (work discipline) influence performance (Y) by 78% while the remaining 22% is influenced by other variables not examined in this research. The results of the t test at a significance level of 0.05 explain that partially (individually) the variables education, motivation and work discipline have a significant influence on the newspaper performance variable because the significant value is smaller than 0.05. The results of the F test at a significance level of 0.05 explain that the variables education, motivation and work discipline have a simultaneous influence (together) on the performance of village government officials because the significant value is smaller than 0.05 and Fcount > Ftable (61.362 > 2.78)